2013
DOI: 10.1016/j.jesp.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Social ecology moderates the association between self-esteem and happiness

Abstract: Previous research has found cross-cultural differences in the strength of the association between self-esteem and happiness. We propose that this difference can be explained by relational mobility, or the degree to which options exist in the given socio-ecological context for relationship formation and dissolution. In Study 1, we found that the association between self-esteem and happiness was stronger among American participants than among Japanese participants. As predicted, this cultural difference was expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 30 publications
3
69
0
Order By: Relevance
“…In this way, our findings implicitly overcome one common criticism of cross-cultural research, whereby within-nation variance in culture is ignored (see admonitions to this effect in Lenartowicz, Johnson, & White, 2003;Tung, 2007). While the present study offers little clues as to the ecological antecedents to within-country relational variance (and by association general trust), future studies might wish to explore possible antecedents such as rural vs. urban environments (Yamagishi, Hashimoto, Li, & Schug, 2012), high vs. low turnover industries (Yuki, Sato, Takemura, & Oishi, 2013), and life-stage differences (Sato & Yuki, 2014).…”
Section: Internet Privacy Concernmentioning
confidence: 55%
See 1 more Smart Citation
“…In this way, our findings implicitly overcome one common criticism of cross-cultural research, whereby within-nation variance in culture is ignored (see admonitions to this effect in Lenartowicz, Johnson, & White, 2003;Tung, 2007). While the present study offers little clues as to the ecological antecedents to within-country relational variance (and by association general trust), future studies might wish to explore possible antecedents such as rural vs. urban environments (Yamagishi, Hashimoto, Li, & Schug, 2012), high vs. low turnover industries (Yuki, Sato, Takemura, & Oishi, 2013), and life-stage differences (Sato & Yuki, 2014).…”
Section: Internet Privacy Concernmentioning
confidence: 55%
“…Lastly, we acknowledge the correlational nature of the mediation analyses in the current study: future work should incorporate experimental methods whereby relational mobility is manipulated in order to establish empirical causation (such as relational mobility priming studies; see Yuki et al, 2013 for an example).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Alternatively, societies high in relational mobility provide people with an abundance of opportunities to meet new people and establish new relationships (Yamagishi & Yamagishi, 1994). Studies have found that relational mobility is useful in explaining a number of differences in psychological and behavioral tendencies among people who live in different societies, such as in the level of trust in strangers , selfenhancement (Falk, Heine, Yuki, & Takemura, 2009), self-disclosure (Schug, Yuki, & Maddux, 2010), determinants of happiness (Sato & Yuki, 2014;Yuki, Sato, Takemura, & Oishi, 2013), reward and punishment of cooperators and defectors (Wang & Leung, 2010), and proneness to shame (Sznycer et al, 2012).…”
Section: Why So Different? a Social-ecological Accountmentioning
confidence: 99%
“…Moreover, higher immigration rates seem to promote further population mobility in terms of self-reinforcing processes (Crowder, Hall, & Tolnay, 2011;Pendakur & Young, 2013). With respect to social structures, residential mobility rates have been related to patterns of independent versus interdependent self-construal (Cousins, 1989;Kashima et al, 2004;Markus & Kitayama, 1991) as well as to relational mobility (i.e., the degree to which a social context provides individuals with options for social relationship formation; Yuki, Sato, Takemura, & Oishi, 2013).…”
Section: The Interplay Of Personality Environments and Mobility At mentioning
confidence: 99%
“…However, based on the personality literature and the presented findings from our own research illustrating substantial personality effects on proximal (social) environment structures, we submit that an individual difference perspective is mandatory for the comprehensive understanding of psychological processes and individual behaviors in proximal social contexts. For example, previous research suggested a link between residential mobility rates and relational mobility (Yuki et al, 2013). However, macro structures that provide high relational mobility might differently affect the social relationship constellations of individuals who are characterized by high levels of Extraversion as compared with others who score low on this trait.…”
Section: Overall Conclusionmentioning
confidence: 99%